The Effects of sodium silicate on Stabilization of organic soil - Pouya Javadzadeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sodium silicate was added to organic soil in order to study its effects on soil shear strength in this research. The different types of soil including sand, clay, peat have been used in this study. Different percentages of sodium silicate (5%, 9%, 12%, 15%) have been used for soil stabilization. In this study, the curing times were 3 days, 7 days, 28 days. Finally, after performing the necessary tests on soil shear strength and comparing the effects of sodium silicate on organic soils, it was observed that soil shear strength has increased after adding sodium silicate gradually. Therefore, lime can be replaced in organic soils to be mixed with sand and clay in with different percentages.